Decreased Radixin Function for ATP‐Binding Cassette Transporters in Liver in Adjuvant‐Induced Arthritis Rats. Issue 12 (20th October 2014) - Kawase, Atsushi; Sakata, Misato; Yada, Nagisa; Nakasaka, Misaki; Shimizu, Takuya; Kato, Yukio; Iwaki, Masahiro
<x xml:space="preserve">Abstract</x> Pathophysiological changes are associated with alterations in the expression and function of numerous ADME‐related proteins. We have previously demonstrated that the membrane localization of ATP‐binding cassette (ABC) transporters in liver was decreased without change of total expression levels in adjuvant‐induced arthritis (AA) in rats. Ezrin/radixin/moesin (ERM) proteins are involved in localization of some ABC transporters in canalicular membrane. The mRNA levels of radixin decreased significantly in liver but not kidney, small intestine, and brain. The mRNA levels of ezrin and moesin did not change in AA. The membrane localization of radixin was reduced in liver of AA and the ratios of activated radixin (p‐radixin) to total radixin were decreased in AA, although the protein levels of radixin did not change in homogenate and membrane protein. To clarify whether AA affects the linker functions of ERM proteins, we examined the interactions between ERM proteins and ABC transporters. The interactions between radixin and ABC transporters were decreased in AA. In vitro studies using human hepatoma HepG2 cells showed that interleukin‐1β decreased the mRNA levels of radixin and colocalization of radixin and Mrp2. Our results show that the decreased radixin functions affect the interaction between radixin and ABC transporters in inflammation. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:4058–4065, 2014